Polyimide-containing molded body for semiconductor element test socket and method for producing same
By using polyylene ester resin material, the problem of deformation and damage of semiconductor equipment test sockets under high energy laser exposure is solved, the high mechanical properties of the material and surface resistance stability are achieved, and the service life of the equipment is extended.
Patent Information
- Application Number
- JP2023563282
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-16
- Filing Date
- 2022-04-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-04-07
AI Technical Summary
The materials of existing semiconductor equipment test sockets have deformation and destruction problems under high voltage and high energy laser intervention, resulting in contact instability and shortened life.
The polyamide resin material formed by polymerization of amino acid compounds and acid diacyl compounds is used to improve the thermal stability and mechanical properties of the material by controlling the polymerization reaction temperature and time, and improve the overall performance of the material through a combination of fill-free combination.
The surface resistance stability and mechanical properties of semiconductor equipment test socket materials under high energy laser exposure have been significantly improved, extending the service life of the equipment.
Smart Images

Figure 0007648798000001 
Figure 0007648798000002 
Figure 0007648798000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a molded article for a semiconductor element test socket, which has excellent mechanical properties and outstanding surface resistance stability, and a method for producing the same. [Background technology]
[0002] Polyimide resin is a highly heat-resistant resin produced by reacting aromatic tetracarboxylic acid or its derivative with aromatic diamine or aromatic diisocyanate, followed by imidization. Polyimide resins can have various molecular structures depending on the type of monomer used.
[0003] Meanwhile, after semiconductor devices are manufactured, various tests are performed to confirm the reliability of the products. Semiconductor device test sockets are used to test electrical signals of semiconductor devices in a non-destructive state of the test socket. During electrical signal testing, the conductive contact portion of the semiconductor device and the upper end of the socket are pressed with an appropriate pressure, and the socket is repeatedly contacted tens of thousands of times or more. In other words, tens to hundreds of conductive pins of the test socket are contacted simultaneously to perform electrical testing.
[0004] Therefore, materials used for semiconductor element test sockets must be resistant to deformations such as distortion that occur under various stress operating conditions, and therefore must have a high flexural modulus, excellent wear resistance, and excellent processability for fine hole processing.
[0005] In addition, in order to be applicable to a dry cleaning system using a laser for removing contaminants from the surface of a test socket after several performance characteristic evaluations of semiconductor devices, the surface resistance stability against the laser must be excellent.
[0006] Therefore, efforts are currently being made to develop materials for semiconductor element test sockets that have the above-mentioned high flexural modulus, excellent dimensional stability, surface stability against high density energy, and excellent processability, in order to improve the yield of the semiconductor manufacturing process and the life of the test sockets.
[0007] However, despite the above efforts, problems such as poor contact or an unstable environment persisting due to distortion or breakage of the test socket, which causes normal semiconductor devices to be treated as defective, etc. Also, when applied to a dry cleaning system, there remains a problem that the surface of the test socket is damaged by a laser, shortening its lifespan.
[0008] As a result, there is a need to develop materials that have good mechanical properties such as flexural modulus and dimensional stability, as well as surface stability against high-density energy and excellent processability. Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention aims to provide a molded article for a semiconductor element test socket which has excellent mechanical properties such as flexural modulus, Young's modulus, tensile strength, and elongation, and which has outstanding surface resistance stability against laser, and a method for producing the same.
[0010] The object of the present invention is not limited to the object mentioned above. The object of the present invention will become clear from the following description and will be realized by the means and combinations thereof described in the claims. [Means for solving the problem]
[0011] The molded body for semiconductor element test socket according to one embodiment of the present invention includes a polyimide resin in which a diamine compound and an acid dianhydride compound are polymerized, and has a surface resistance of 1×10 when exposed to a laser having an energy of 200 mJ to 500 mJ more than 5,000 times. 9 It may be Ω / sq or more.
[0012] The molded article may have a moisture absorption rate of 0.15% or less.
[0013] The molded article may have a flexural modulus of 5,000 MPa to 6,000 MPa, a Young's modulus of 3,000 MPa to 4,000 MPa, a tensile strength of 100 to 200 MPa, and an elongation rate of 4% to 10%.
[0014] The molded article may contain no filler.
[0015] The diamine compound may contain 60% to 80% by weight of paraphenylenediamine (p-PDA) and 20% to 40% by weight of metaphenylenediamine (m-PDA).
[0016] The acid dianhydride compound may contain 50% to 60% by weight of biphthalic dianhydride (BPDA) and 40% to 50% by weight of pyromellitic dianhydride (PMDA).
[0017] A method for manufacturing a molded body for a semiconductor device test socket according to an embodiment of the present invention may include: polymerizing a diamine compound and an acid dianhydride compound to prepare a polyimide resin; and molding the polyimide resin.
[0018] The step of preparing the polyimide resin may include a step of heating a solution containing the diamine compound and the acid dianhydride compound to a temperature of 90° C. to 120° C. at a rate of 2° C. / min to 6° C. / min to perform a first reaction; and a step of heating the resultant to a temperature of 140° C. to 180° C. at a rate of 2° C. / min to 6° C. / min to perform a second reaction.
[0019] The method may further include a step of baking the molded polyimide resin.
[0020] The baking step may involve baking the molded polyimide resin in a nitrogen atmosphere at a temperature of 300° C. to 500° C. for 5 hours to 15 hours. Effect of the Invention
[0021] According to the present invention, it is possible to obtain a molded article for a semiconductor element test socket which is excellent in mechanical properties such as flexural modulus, Young's modulus, tensile strength and elongation, and has outstanding surface resistance stability against laser.
[0022] The effects of the present invention are not limited to those mentioned above, and it will be understood that the effects of the present invention include any effects that can be inferred from the following description. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The above objects, other objects, features and advantages of the present invention will be easily understood from the following preferred embodiments in conjunction with the accompanying drawings. However, the present invention is not limited to the embodiments described herein and may be embodied in other forms. Rather, the embodiments introduced herein are provided so that the disclosed contents can be thorough and complete, and so that the idea of the present invention can be fully conveyed to those skilled in the art.
[0024] While describing each figure, like reference numerals are used for like components. In the accompanying drawings, the dimensions of structures are shown exaggerated for clarity of the present invention. Terms such as first and second may be used to describe various components, but these components should not be limited by such terms. These terms are used only for the purpose of distinguishing one component from another component. For example, the first component may be named the second component, and similarly, the second component may be named the first component, without departing from the scope of the present invention. A singular expression includes a plural expression unless otherwise specified in the context.
[0025] In this specification, the terms "comprise" or "have" are intended to specify the presence of a feature, number, step, operation, component, part, or combination thereof described in the specification, and should be understood as not precluding the presence or addition of one or more other features, numbers, steps, operations, components, parts, or combinations thereof. In addition, when a layer, film, region, plate, or other part is described as being "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part between them. Similarly, when a layer, film, region, plate, or other part is described as being "under" another part, this includes not only the case where it is "directly under" the other part, but also the case where there is another part between them.
[0026] Unless otherwise stated, all numbers, values and / or expressions expressing amounts of ingredients, reaction conditions, polymer compositions and formulations used herein should be understood in all cases to be modified by the term "about" in that these numbers are approximations reflecting various uncertainties of measurement that arise in obtaining such values from disparate entities. Also, when numerical ranges are disclosed in this description, such ranges are continuous and include all values from the minimum value to the maximum value, including the maximum value, unless otherwise stated. Furthermore, when such ranges indicate integers, they include all integers from the minimum value to the maximum value, including the maximum value, unless otherwise stated.
[0027] The molded article for semiconductor element test socket according to the present invention contains a polyimide resin in which a diamine compound and an acid dianhydride compound are polymerized, and has a surface resistance of 1×10 when exposed to a laser having an energy of 200 mJ to 500 mJ 5,000 times or more. 9 It is characterized by being Ω / sq or more.
[0028] The surface resistance of the molded body is measured to confirm that the surface is not damaged. If the surface of the molded body is damaged, the surface resistance will be low. When the molded body is exposed to a laser having a predetermined energy, the surface resistance is 1×10 9The surface resistance of the molded article is not particularly limited, and may be, for example, 1×10 10 Ω / sq or less, or 1×10 11 Ω / sq or less, or 1×10 12 It may be Ω / sq or less.
[0029] The molded article is also characterized in that its moisture absorption rate is 0.15% or less. Although there is a trade-off between the stability of surface resistance and the moisture absorption rate, the present invention appropriately adjusts the content of the components constituting the polyimide to improve the stability of surface resistance and the moisture absorption rate in a well-balanced manner. The lower limit of the moisture absorption rate is not particularly limited, and may be, for example, 0.01% or more, 0.05% or more, or 0.10% or more.
[0030] The molded article is characterized by having a flexural modulus of 5,000 MPa to 6,000 MPa, a Young's modulus of 3,000 MPa to 4,000 MPa, a tensile strength of 100 to 200 MPa, and an elongation of 4% to 10%. The molded article has such excellent mechanical properties and exhibits outstanding dimensional stability even under various stress operating conditions.
[0031] The polyimide resin contained in the molded product will now be described in detail.
[0032] The polyimide resin may be a polymer of a diamine compound and an acid dianhydride compound.
[0033] The diamine compound is a mixture containing one or more aromatic diamine monomers, and may include at least one selected from the group consisting of 4,4-oxydianiline (ODA), paraphenylenediamine (p-PDA), metaphenylenediamine (m-PDA), 4,4-methylenedianiline (MDA), 2,2-bisaminophenylhexafluoropropane (HFDA), meta-bisaminophenoxydiphenylsulfone (m-BAPS), para-bisaminophenoxydiphenylsulfone (p-BAPS), 1,4-bisaminophenoxybenzene (TPE-Q), bisaminophenoxybenzene (TPE-R), 2,2-bisaminophenoxyphenylpropane (BAPP), 2,2-bisaminophenoxyphenylhexafluoropropane (HFBAPP), 4,4-benzanilide (DABA), and combinations thereof.
[0034] Specifically, the diamine compound may contain 60% by weight to 80% by weight of paraphenylenediamine (p-PDA) and 20% by weight to 40% by weight of metaphenylenediamine (m-PDA). By adjusting the content of each component of the diamine compound in this manner, the surface resistance, moisture absorption rate, and mechanical properties can be uniformly improved.
[0035] The acid dianhydride compound is a mixture containing one or more aromatic tetracarboxylic dianhydride monomers, and may include at least one selected from the group consisting of pyromellitic dianhydride (PMDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), biphthalic dianhydride (BPDA), hexafluoroisopropylidenediphthalic dianhydride (6-FDA), and combinations thereof.
[0036] Specifically, the acid dianhydride compound may contain 50% by weight to 60% by weight of biphthalic dianhydride (BPDA) and 40% by weight to 50% by weight of pyromellitic dianhydride (PMDA). By setting the content of each component of the acid dianhydride compound in this manner, it is possible to improve mechanical properties such as flexural modulus and elongation of the molded product without using a filler.
[0037] The polyimide resin may be represented by the following Chemical Formula 1. [Chemical formula 1] [ka]
[0038] In the above formula 1, [ka] It may be selected from the group consisting of:
[0039] [ka] wherein n is selected from the group consisting of:
[0040] Specifically, the polyimide resin may include at least one of those represented by the following Chemical Formulas 2 to 5.
[0041] [Chemical formula 2] [ka]
[0042] [Chemical formula 3] [ka]
[0043] [Chemical formula 4] [ka]
[0044] [Chemical formula 5] [ka]
[0045] The a to d may each be 100 to 550.
[0046] The polyimide resin has an intrinsic viscosity of 0.7 dl / g to 2.5 dl / g, a crystallinity of 20% to 30%, and a specific surface area (based on the powdered polyimide resin) of 50 m 2 / g~400m 2 The polyimide resin has a low crystallinity, a high imidization degree and a specific surface area, and therefore has excellent moldability and can be effectively compression molded.
[0047] The method for manufacturing a molded article for a semiconductor device test socket according to the present invention may include the steps of polymerizing a diamine compound and an acid dianhydride compound to prepare a polyimide resin, and molding the polyimide resin.
[0048] The present invention is characterized in that, when producing the polyimide resin, the temperature of a solution containing a diamine compound and an acid dianhydride compound is gradually increased to carry out imidization polymerization, thereby significantly improving the heat resistance, mechanical properties such as flexural modulus, and surface resistance stability of the molded product.
[0049] Specifically, the step of preparing the polyimide resin may include the steps of dissolving a diamine compound in a solvent, providing an acid dianhydride thereto to obtain a solution, subjecting the solution to a first reaction at a predetermined temperature, and subjecting a resultant of the first reaction to a second reaction at a temperature higher than that of the first reaction.
[0050] First, a diamine compound is placed in a reactor equipped with a stirrer, a temperature controller, a nitrogen injector, etc., and completely dissolved in a solvent, and then nitrogen gas is passed through the solution at room temperature and stirred for 30 minutes.
[0051] In this case, the solvent may include a polar solvent. The polar solvent is not particularly limited as long as it is an organic polar solvent having a high boiling point. For example, the polar solvent may include at least one selected from the group consisting of mixed cresols, mixed xylenes, N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), dimethylacetamide (DMAc), dimethylsulfoxide (DMSO), diethyl acetate (DEA), and 3-methoxy-N,N-dimethylpropanamide (DMPA).
[0052] After dissolving the diamine compound, the solution is heated for 1 to 2 hours to raise the temperature to 60° C. to 80° C., and an acid dianhydride is added thereto to obtain a solution. At this time, the solid content of the solution may be 6% by weight to 16% by weight, or 8% by weight to 12% by weight.
[0053] Thereafter, the solution is heated to 90°C to 120°C at a rate of 2°C / min to 6°C / min to carry out a primary reaction for 2 to 3 hours, and the resultant is heated to 140°C to 180°C at a rate of 2°C / min to 6°C / min to carry out a secondary reaction for 1 to 2 hours to obtain a polyimide resin. Preferably, the solution is heated to 90°C to 120°C at a rate of 3°C / min to 5°C / min to carry out a primary reaction for 2 to 3 hours, and the resultant is heated to 160°C to 180°C at a rate of 3°C / min to 5°C / min to carry out a secondary reaction for 1 to 2 hours to obtain a polyimide resin.
[0054] In this case, a catalyst may be added to the solution in order to increase the reactivity of the imidization reaction. The catalyst is not particularly limited as long as it can improve the reactivity without significantly impairing the object and effect of the present invention. For example, the catalyst may be selected from the group consisting of trimethylamine, xylene, pyridine, quinoline, and combinations thereof. In the present invention, in addition to the catalyst, any one selected from the group consisting of a plasticizer, an antioxidant, a flame retardant, a dispersant, a viscosity modifier, a leveling agent, and combinations thereof may be further included, and this may also be selected and used as necessary within a range that does not significantly impair the object and effect of the present invention.
[0055] After the imidization reaction is completed, the polyimide resin can be filtered and washed with an organic solvent. The organic solvent used here is not particularly limited as long as it has a low boiling point. Examples of the organic solvent include acetone and methyl alcohol.
[0056] After washing the polyimide resin, the washed polyimide resin was -1 The drying can be performed under a pressure of Torr or less, in a nitrogen gas atmosphere, and at a temperature of 100° C. to 250° C. The drying temperature is preferably 160° C. to 220° C., and more preferably 170° C. to 200° C.
[0057] The dried polyimide resin was -1 ~10 3 The drying can be carried out at a pressure of 10 Torr, in a nitrogen gas atmosphere, and at a temperature of 250° C. to 400° C. Preferably, the drying temperature and pressure are 280° C. to 370° C. and 10 to 10 3 Torr, more preferably 300°C to 350°C and 10 2 ~10 3 Torr.
[0058] The polyimide resin can then be molded into a desired shape. The method for producing a molded article according to the present invention may further include a step of baking the molded polyimide resin. Specifically, the polyimide resin can be compression molded at a pressure of 50,000 psi to 100,000 psi, and the compression molded polyimide resin can be baked in a nitrogen atmosphere at a temperature of 300°C to 500°C for 5 hours to 15 hours. This makes it possible to produce a molded article with excellent heat resistance and mechanical properties. Meanwhile, the compression molding and baking may be carried out simultaneously to produce a molded article.
[0059] The molded article according to the present invention can be used as a core heat-resistant part in various cutting-edge industrial fields such as the electrical and electronics industry, the automobile industry, the semiconductor industry, and the aerospace industry, in addition to the semiconductor device test socket.
[0060] The present invention will be described in more detail with reference to the following specific examples. The following examples are merely illustrative to aid in understanding the present invention, and are not intended to limit the scope of the present invention.
[0061] Example 1: p-PDA (80%) / m-PDA (20%)+BPDA (50%) / PMDA (50%) In a 2-liter reactor equipped with an agitator, temperature control device, and nitrogen injection device, 29.59 g of paraphenylenediamine (p-PDA) and 7.39 g of metaphenylenediamine (m-PDA) are placed and dissolved in 672.4 g of N-methyl-2-pyrrolidone (NMP). Then, 448.3 g of mixed xylene is added and nitrogen gas is passed through at room temperature. 37.31 g of pyromellitic dianhydride (PMDA) and 50.32 g of biphthalic dianhydride (BPDA) are injected while gradually increasing the temperature to 60-80°C at room temperature for 1-2 hours. In this case, the solid concentration is fixed at 10% by weight, and the reaction is carried out at 60-80°C for 1-2 hours. The temperature of the reaction solution is gradually raised to 90-120°C at a rate of 3°C / min and stirred for 2-3 hours. The temperature is then raised to 160-180°C at a rate of 3°C / min, and the mixture is stirred for 1-2 hours to carry out the imidization reaction. When the reaction is completed, the precipitated polyimide polymer is filtered and washed with 2 liters of acetone, and then the mixture is heated at 190°C for 10 minutes. -1 The mixture was dried for 16 hours under a vacuum of 1000 torr and a nitrogen stream. After drying, the mixture was re-dried at 300°C for 10 minutes before molding. 3 The powder was dried under a nitrogen stream at Torr for 8 hours. The intrinsic viscosity of the polyimide resin powder was 1.7 dl / g, measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent, and the degree of imidization was 99%. The powder was molded at a pressure of 100,000 psi and sintered at 400°C for 11 hours to produce a molded product.
[0062] Example 2: p-PDA (75%) / m-PDA (25%)+BPDA (60%) / PMDA (40%) A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. The polyimide resin powder according to Example 2 had an intrinsic viscosity of 1.7 dl / g and an imidization degree of 99% measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded at a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0063] Example 3: p-PDA (75%) / m-PDA (25%)+BPDA (50%) / PMDA (50%) A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. The polyimide resin powder according to Example 3 had an intrinsic viscosity of 1.8 dl / g and an imidization degree of 99% when measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded at a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0064] Example 4: p-PDA (70%) / m-PDA (30%)+BPDA (60%) / PMDA (40%) A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. The polyimide resin powder of Example 4 had an intrinsic viscosity of 1.7 dl / g and an imidization degree of 99% when measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded at a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0065] Example 5: p-PDA (70%) / m-PDA (30%)+BPDA (55%) / PMDA (45%) A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. The polyimide resin powder of Example 5 had an intrinsic viscosity of 1.7 dl / g and an imidization degree of 99% when measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded at a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0066] Example 6: p-PDA (70%) / m-PDA (30%)+BPDA (50%) / PMDA (50%) A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. The polyimide resin powder of Example 6 had an intrinsic viscosity of 1.7 dl / g and an imidization degree of 99% when measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded at a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0067] Example 7: p-PDA (60%) / m-PDA (40%)+BPDA (50%) / PMDA (50%) A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. The polyimide resin powder of Example 7 had an intrinsic viscosity of 1.7 dl / g and an imidization degree of 99% when measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded at a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0068] Comparative Example 1 A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. The polyimide resin powder according to Comparative Example 1 had an intrinsic viscosity of 1.1 dl / g and an imidization degree of 99% when measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded under a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0069] Comparative Example 2 A polyimide resin was prepared in the same manner as in Example 1, except that the composition of the diamine compound and the acid dianhydride compound was adjusted as shown in Table 1 below. Specifically, 4,4-oxydianiline (ODA) was added instead of metaphenylenediamine (m-PDA), but its content was adjusted, and only biphthalic dianhydride (BPDA) was used as the acid dianhydride compound. The polyimide resin powder according to Comparative Example 2 had an intrinsic viscosity of 1.2 dl / g and an imidization degree of 99% measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded at a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0070] Comparative Example 3 A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. Specifically, only 4,4-oxydianiline (ODA) was used as the diamine compound, and only pyromellitic dianhydride (PMDA) was used as the acid dianhydride compound. The polyimide resin powder according to Comparative Example 3 had an intrinsic viscosity of 1.4 dl / g and an imidization degree of 99% measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded at a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0071] Comparative Example 4 A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. The polyimide resin powder according to Comparative Example 4 had an intrinsic viscosity of 1.3 dl / g and an imidization degree of 99% when measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded under a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0072] Comparative Example 5 A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. The polyimide resin powder according to Comparative Example 5 had an intrinsic viscosity of 1.9 dl / g and an imidization degree of 99% when measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded under a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0073] Comparative Example 6 A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. The polyimide resin powder according to Comparative Example 6 had an intrinsic viscosity of 1.7 dl / g and an imidization degree of 99% when measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded under a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0074] Comparative Example 7 A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. The polyimide resin powder according to Comparative Example 7 had an intrinsic viscosity of 1.7 dl / g and an imidization degree of 99% when measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded under a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0075] Comparative Example 8 A polyimide resin was prepared in the same manner as in Example 1, except that the compositions of the diamine compound and the acid dianhydride compound were adjusted as shown in Table 1 below. The polyimide resin powder according to Comparative Example 8 had an intrinsic viscosity of 1.5 dl / g and an imidization degree of 99% when measured at 30°C at a concentration of 0.2 g / dl using concentrated sulfuric acid as a solvent. The powder was molded under a pressure of 100,000 psi and sintered at 400°C for 11 hours to prepare a molded product.
[0076] [Table 1]
[0077] The surface resistance stability was evaluated by a laser exposure test for the molded articles of Examples 1 to 7 and Comparative Examples 1 to 8. Specifically, each molded article was exposed to a laser under conditions of an energy intensity of 200 mJ and an exposure frequency of 5 times per second, and the surface resistance was 1×10 9 The number of exposures that maintained a resistance above Ω / sq was measured, and the results are shown in Table 2.
[0078] The tensile strength, elongation, flex modulus and water absorption rate of the molded articles of Examples 1 to 7 and Comparative Examples 1 to 8 were measured in accordance with ASTM D1708, ASTM D790 and ASTM D570. The results are shown in Table 2.
[0079] [Table 2]
[0080] Referring to Table 2, Comparative Examples 1 and 2 are excellent in mechanical properties and moisture absorption rate, but are very poor in surface stability, whereas Comparative Example 3 is excellent in surface stability, but does not reach the desired levels in flex modulus, Young's modulus, and elongation.
[0081] Moreover, it is apparent that Comparative Examples 4 to 8 are somewhat inferior to Examples 1 to 7 in terms of surface stability.
[0082] As a result, the present invention has discovered an effective composition for producing a polyimide resin powder having a high flexural modulus, excellent dimensional stability, surface stability against high density energy, and excellent processability without using a filler, and it can be seen that the present invention is a new production method that is simpler than conventional techniques, is economically competitive, and produces products with excellent physical properties.
[0083] Although the embodiments of the present invention have been described in detail above, the scope of the present invention is not limited to the above-described embodiments, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the appended claims are also included in the scope of the present invention.
Claims
1. The polyimide resin includes a diamine compound and an acid dianhydride compound polymerized therein, When exposed to a laser with an energy of 200 mJ to 500 mJ more than 5,000 times, the surface resistance is 1 x 10 9 Ω / sq or more, The diamine compound comprises 60% by weight to 80% by weight of paraphenylenediamine (p-PDA) and 20% by weight to 40% by weight of metaphenylenediamine (m-PDA); The acid dianhydride compound comprises 50% by weight to 60% by weight of biphthalic dianhydride (BPDA) and 40% by weight to 50% by weight of pyromellitic dianhydride (PMDA),
2. 2. The molded article for a semiconductor element test socket according to claim 1, which has a moisture absorption rate of 0.15% or less.
3. 2. The molded article for semiconductor element test sockets according to claim 1, having a flexural modulus of 5,000 MPa to 6,000 MPa, a Young's modulus of 3,000 MPa to 4,000 MPa, a tensile strength of 100 to 200 MPa, and an elongation rate of 4% to 10%.
4. 2. The molded article for a semiconductor element test socket according to claim 1, which does not contain a filler.
5. Polymerizing a diamine compound and an acid dianhydride compound to prepare a polyimide resin; and molding the polyimide resin; When exposed to a laser with an energy of 200 mJ to 500 mJ more than 5,000 times, the surface resistance is 1 x 10 9 Ω / sq or more, The diamine compound comprises 60% by weight to 80% by weight of paraphenylenediamine (p-PDA) and 20% by weight to 40% by weight of metaphenylenediamine (m-PDA); The acid dianhydride compound comprises 50% by weight to 60% by weight of biphthalic dianhydride (BPDA) and 40% by weight to 50% by weight of pyromellitic dianhydride (PMDA).
6. The method for producing a molded article for a semiconductor element test socket according to claim 5, wherein the moisture absorption rate is 0.15% or less.
7. The method for producing a molded article for a semiconductor element test socket according to claim 5, wherein the bending modulus is 5,000 MPa to 6,000 MPa, the Young's modulus is 3,000 MPa to 4,000 MPa, the tensile strength is 100 to 200 MPa, and the elongation is 4% to 10%.
8. The step of preparing the polyimide resin comprises: A step of heating the solution containing the diamine compound and the acid dianhydride compound to a temperature of 90° C. to 120° C. at a rate of 2° C. / min to 6° C. / min to perform a primary reaction; and 6. The method of claim 5, further comprising the step of: raising the temperature of the resultant product to 140° C. to 180° C. at a rate of 2° C. / min to 6° C. / min to carry out a secondary reaction.
9. 6. The method for producing a molded article for a semiconductor element test socket according to claim 5, wherein the polyimide resin does not contain a filler.
10. 6. The method of claim 5, further comprising the step of baking the molded polyimide resin.
11. 11. The method of claim 10, wherein the baking step bakes the molded polyimide resin in a nitrogen atmosphere at a temperature of 300° C. to 500° C. for 5 hours to 15 hours.
Citation Information
Patent Citations
Method for producing a fully aromatic polyimide resin with improved heat resistance and tensile properties in high-temperature regions.
JP2013516508A
Polyimide powder having high thermooxidative stability
JP2015129277A
Polyimide composition and polyimide test socket housing
JP2019526163A